Analysis of Ocean Tide‐Induced Magnetic Fields Derived From Oceanic In Situ Observations : Climate Trends and the Remarkable Sensitivity of Shelf Regions - Petereit, Johannes; Saynisch‐Wagner, Jan; Irrgang, Christopher; Thomas, Maik (Freie Universität Berlin, 2019)
Tidal motion of oceanic salt water through the ambient geomagnetic field induces periodic electromagnetic field signals. Amplitudes of the induced signals are sensitive to variations in electrical seawater conductivity and, consequently, to changes in oceanic temperature and salinity. In this paper, we computed and analyzed time series of global ocean tide‐induced magnetic field amplitudes. For this purpose, we combined data of global in situ observations of oceanic temperature and salinity fields from 1990–2016 with data of oceanic tidal flow, the geomagnetic field, mantle conductivity, and sediment conductance to derive ocean tide‐induced magnetic field amplitudes. The results were used to compare present day developments in the oceanic climate with two existing climate model scenarios, namely, global oceanic warming and Greenland glacial melting. Model fits of linear and quadratic long‐term trends of the derived magnetic field amplitudes show indications for both scenarios. Also, we find that magnetic field amplitude anomalies caused by oceanic seasonal variability and oceanic climate variations are 10 times larger in shallow ocean regions than in the open ocean. Consequently, changes in the oceanic and therefore the Earth's climate system will be observed first in shelf regions. In other words, climate variations of ocean tide‐induced magnetic field amplitudes are best observed in shallow ocean regions using targeted monitoring techniques.